Contributions of Residential and Income Mobility in Different Life Stages to Increasing Low-Income Rates in Suburban Neighbourhoods - Kauppinen, Timo M.; Karhula, Aleksi (WILEY, 2025)
Socioeconomic residential segregation has been increasing in many cities in Europe and globally. Selective migration is usually considered the main mechanism shaping the socioeconomic trajectories of neighbourhoods, although some studies have suggested it to have only minor contributions. However, it is worth looking, how persons in different life course situations affect these trajectories by their moves or income mobility. Living in a low-income neighbourhood may be related to a 'transit stage' in the life course, for example in the beginning of the work, housing, and family careers, and if the declining income level in the neighbourhood is related to such situations, it may be less indicative of problems in the area. This study explores how selective migration and income mobility have contributed to the income trajectories of suburban neighbourhoods experiencing downward trend in their income level in Finnish cities between 1997 and 2019, and how these contributions are related to different life course situations. We use individual-level register-based panel data covering the complete population of Finland and decomposition methods. Our findings emphasise the central role of selective migration in the increasing low-income rates. Particularly the residential mobility of young childless adults, commonly students, has increased the low-income populations. However, the main difference to other types of neighbourhoods is the net loss of employed middle-aged Finnish-born non-low-income residents. This calls for policies improving the attractiveness of these neighbourhoods for the non-low-income population.